Relationship between quality factors in graduate teaching and learning and students’ satisfaction in research universities - Zhalehpour, Sousan (2014)
Exploring the factors that influence students’ satisfaction with teaching and learning has been one of the main focuses of researchers and educators. However, there is limited knowledge on the factors that affect students’ satisfaction specifically in research universities. This study aims to explore the factors that influence student’s satisfaction in Malaysian research universities. A questionnaire with 130 items was utilized to measure four dimensions of quality factors (facilities, human-based, system-based and student’s skills acquisition) and students’ satisfaction (11 items). A total of 305 postgraduate students from three Malaysian universities (UPM, UM, UKM) were asked to respond to the questionnaire on a five-point likert scale ranging from 1(strongly disagree) to 5 (strongly agree). The findings indicated a significant moderate correlation between quality factors of teaching and learning and students’ satisfaction. A multiple regression equation for prediction of quality factors in teaching and learning was utilized in which four dimensions of quality factors (facilities, human-based factors, system-based factors and students’ skills acquisition) are treated as independent variables and students’ satisfaction as dependent variable. Moreover, the findings indicated that quality factors related to teaching and learning in research universities have a significant relationship with students’ satisfaction. The implications of the findings for improving the quality of teaching and learning in Malaysian research universities as well as graduate students’ satisfaction are discussed and recommended. These implications include the influential role of quality factors that affect students’ pedagogical improvement. Also, the component of quality factors as proposed and tested by this research including facilities, humanbased factors, system-based factors and students’ skills satisfaction factors could assist scholars to consider the influence of these factors in shaping students satisfaction and lead to the development of a theory for students’ satisfaction. Furthermore, this study may help educational researchers specifically in Malaysia through evaluating validity and reliability of quality factors of teaching and learning and students’ satisfaction scale. Research university educators may specifically use the results of this study in designing more effective research education and training programs. And to be aware of the importance of the factors that affect students’ satisfaction improvement and provide them with the specific needs of students in research universities. The findings that supervisors have a significant influence on students’ satisfaction improvement will help educators enhance supervisors’ awareness of the key role that they can play in shaping students’ satisfaction and empower them with the skills to effectively manage their interactions with students. Other Malaysian university students may become aware of the influential factors in the university that facilitate their satisfaction improvement and more effectively learn research knowledge and skills. This study suggested the significant relationship between age (students between 31 and 40 years old) and human-based factors in research universities. This finding can help educators in providing young students (below 31 years old) with the short courses and workshops on managing their relationships with their supervisors and lecturers in order to improve their satisfaction with these factors. The finding that international students had the lowest satisfaction with these factors should be considered by educators and policy maker if they are to attract more international students to Malaysian universities as suggested by the country’s Vision 2020.